Critical Closing Pressure as a Proxy for paco2 in Non-Linear Multivariate Models for Estimation of Dynamic Cerebral Autoregulation and Cerebrovascular Reactivity - Chacon-Pacheco, M; Bello-Robles, F (ELSEVIER SCIENCE BV, 2015)
Sin Resumen Disponible